(Neuro)Aesthetics: Beauty, ugliness, and ethics. Issue 5 (19th August 2021) - Dietrich, Philip; Knieper, Thomas
Abstract: The objective of this essay is a holistic view of aesthetics, ethics, and neuroaesthetics. After a few introductory case studies, aesthetics is systematically introduced as a philosophical subdiscipline. This perspective is then expanded from aesthetics to neuroaesthetics. Using various art forms as well as current media formats, the aspects of beauty and ugliness are discussed, and aesthetic properties are expanded to include ethical implications. These can be expressed through ideals of beauty and the compulsion for body transformation. This perspective is then expanded from aesthetics to neuroaesthetics. From this point of view of art, the so‐called golden ratio will play a central role. It will be shown how representations affect people and what ethical implications are associated with the effects. Therefore, this essay first has to look at art from the perspective of neuroaesthetics, and then consider the ethical aspects of the beautiful and the ugly. The considerations lead to a brief discussion of Socrates's three sieves.